Telerehabilitation for Knee Osteoarthritis in Brazil: A Feasibility Study - Aily, Jéssica Bianca; Barton, Christian John; Mattiello, Stela Marcia; de Oliveira Silva, Danilo; de Noronha, Marcos (International Journal of Telerehabilitation, 2020)
Background: The effectiveness of telerehabilitation for a patient with knee osteoarthritis may depend upon the person’s adherence to intervention. Thus, the aim of this study was to investigate whether people with knee osteoarthritis would adhere to exercise-therapy facilitated via multiple media in Brazil, a newly industrialized country. Method: This is a feasibility study, pre-post intervention. Middle aged (40-50 years) and elderly (?70 years) people with knee osteoarthritis received in-person exercise-therapy instructions on the first day, along with a booklet and DVD (videos) to take home. Participants also received six motivational phone calls throughout the 12-week treatment. Satisfaction and adherence were assessed one week after intervention with the Exercise Adherence Rating Scale (EARS), sections B and C. Preference on the method used to adhere to exercises was recorded. Conclusion: Telerehabilitation was well accepted by middle-aged and elderly Brazilians with knee osteoarthritis. The preferred media to enhance adherence, was a booklet with descriptions of the exercises, especially for the elderly cohort.